IMPACT OF HAND-TO-HAND COMBAT PROGRAMS ON CADETS’ PROFESSIONAL COMPETENCE AND OPERATIONAL READINESS (World Bulletin of Physical Education and Sports Science, 2026)
This study investigates the impact of hand-to-hand combat (HHC) training programs on the professional competence and operational readiness of law enforcement cadets. The research evaluates physical fitness, tactical skills, and functional preparedness before and after a structured HHC training intervention. Results indicate significant improvements in endurance, strength, agility, and task-specific competencies, demonstrating the effectiveness of HHC programs as an essential tool in cadet professional development.
Keywords: Hand-to-hand combat, Cadets, Professional competence, Operational readiness, Physical fitness, Tactical skills, Functional preparedness, Law enforcement training.